Integrative analysis based on ATAC-seq and RNA-seq reveals a novel oncogene PRPF3 in hepatocellular carcinoma - Yi Bai; Xiyue Deng; Dapeng Chen; Shuangqing Han; Zijie Lin; Zhongmin Li; Wen Tong; Jinming Li; Tianze Wang; Xiangyu Liu; Zirong Liu; Zilin Cui; et al. (Clinical Epigenetics)
Abstract Background Assay of Transposase Accessible Chromatin Sequencing (ATAC-seq) is a high-throughput sequencing technique that detects open chromatin regions across the genome. These regions are critical in facilitating transcription factor binding and subsequent gene expression. Herein, we utilized ATAC-seq to identify key molecular targets regulating the development and progression of hepatocellular carcinoma (HCC) and elucidate the underlying mechanisms. Methods We first compared chromatin accessibility profiles between HCC and normal tissues. Subsequently, RNA-seq data was employed to identify differentially expressed genes (DEGs). Integrating ATAC-seq and RNA-seq data allowed the identification of transcription factors and their putative target genes associated with differentially accessible regions (DARs). Finally, functional experiments were conducted to investigate the effects of the identified regulatory factors and corresponding targets on HCC cell proliferation and migration. Results Enrichment analysis of DARs between HCC and adjacent normal tissues revealed distinct signaling pathways and regulatory factors. Upregulated DARs in HCC were enriched in genes related to the MAPK and FoxO signaling pathways and associated with transcription factor families like ETS and AP-1. Conversely, downregulated DARs were associated with the TGF-β, cAMP, and p53 signaling pathways and the CTCF family. Integration of the datasets revealed a positive correlation between specific DARs and DEGs. Notably, PRPF3 emerged as a gene associated with DARs in HCC, and functional assays demonstrated its ability to promote HCC cell proliferation and migration. To the best of our knowledge, this is the first report highlighting the oncogenic role of PRPF3 in HCC. Furthermore, ZNF93 expression positively correlated with PRPF3, and ChIP-seq data indicated its potential role as a transcription factor regulating PRPF3 by binding to its promoter region. Conclusion This study provides a comprehensive analysis of the epigenetic landscape in HCC, encompassing both chromatin accessibility and the transcriptome. Our findings reveal that ZNF93 promotes the proliferation and motility of HCC cells through transcriptional regulation of a novel oncogene, PRPF3.